Peran Digitalisasi dalam Meningkatkan Daya Tarik Wisatawan di Taman Mini Indonesia Indah - Ariawan Aryapranata; Fachrul Husain Habibie; Arief Faizal Rachman; Linda Desafitri Ratu Bilqis; Yuliansyah AL Rasyid (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
This study aims to analyze the role of digitalization in enhancing tourist attractiveness at Taman Mini Indonesia Indah (TMII) following its revitalization. Digitalization has become an important strategy in the development of modern tourism destinations through the utilization of information technology, social media, digital service systems, and interactive technologies that support tourist experiences. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving destination managers, tourists, and individuals with knowledge of digital tourism and smart tourism implementation. The findings reveal that digitalization at TMII is manifested through the implementation of e-ticketing systems, social media platforms, destination websites, digital information services, interactive technologies, and data-driven management. These implementations contribute to enhancing tourist attractiveness through four main mechanisms: improved access to information, greater service convenience, enhanced tourist experiences, and increased visitor satisfaction. Digitalization also supports the realization of smart tourism through the effective integration of technology, information, and tourism services. This study concludes that digitalization serves as a strategic factor in strengthening tourist attractiveness and improving the competitiveness of cultural tourism destinations in the era of digital transformation. Keywords: tourism digitalization, smart tourism, tourist attraction, tourist experience